The role of g-C3N4 in round-the-clock photocatalysis for POME. Issue 1 (April 2021) - Razali, N A M; Salleh, W N W; Rosman, N; Ismail, H; Ahmad, S Z N; Aziz, F; Lau, W J; Ismail, A F
Abstract: The main drawback of conventional palm oil mill effluent (POME) treatment is that the process is time and space-consuming. Besides, the treatment produces highly polluted wastewater that pollutes the environment if discharged directly. Photocatalytic process has significant potential to degrade recalcitrant organic pollutants and has recently attracted tremendous attention. However, current approaches mainly focus on visible light condition, which is still an ineffective treatment for POME. In this study, POME was successfully degraded using graphitic carbon nitride (g-C3 N4 ) photocatalyst synthesised by calcination. The prepared photocatalyst was characterised by ultraviolet-visible diffuse reflectance (UV-Vis DRS) spectroscopy and scanning electron microscopy (SEM). The SEM results revealed the morphology of g-C3 N4 photocatalyst. g-C3 N4 could act as a visible-light-driven (VLD) photocatalyst with the highest photocatalytic efficiency of 71% under visible light. The present work highlights the potential of g-C3 N4 towards the degradation of POME under visible light and dark condition. The highly enhanced photocatalytic performance is attributed to g-C3 N4, but it does not work well in round-the-clock photocatalysis. However, g-C3 N4 can work as the band alignment to drive separate photogenerated charge carriers, leading to effective photocatalytic degradation. g-C3 N4 photocatalyst may be considered as an ideal candidate for treating POME.